Coordinación grafoperceptiva: incidencia en el desarrollo de la motricidad fina en niños de 5 a 6 años de edad - Ramírez-Aguirre, Gardenia; Gutiérrez-Cedeño, Maritza; León-Piguave, Ana; Vargas-Cruz, Michell; Cetre-Vásquez, Roxana (Ciencia UNEMI, 2017)
This paper aims to determine the incidence of grapho-perceptive coordination in the proper development of daily school activities of children 5-6 years of age in a Basic Education institution in the canton Milagro, Ecuador. The poor development of fine motor skills is a matter of concern, since it has generated difficulties in school activities and tasks. Each activity that includes fine motor skills form a compendium of knowledge that will result in the acquisition of new skills and abilities. In this predominantly qualitative, field-based, descriptive and cross-sectional research, interviews, surveys and observation records were applied to teachers, parents, students and experts in the area It is concluded that infants show little creativity in graphoplastic activities, a situation evidenced in the lack of interest shown in practices for the development of fine motor, essential for the process of reading and writing.